Pengaruh Kepemimpinan Partisipatif terhadap Perilaku Berbicara dengan Berbagi Pengetahuan sebagai Variabel Mediasi pada PT. Jambi Ekspres Televisi - Saputra, Andika Surya; Hasanah, Nur; Rts. Ratnawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the impact of participative leadership on voice behavior with knowledge sharing as a mediating variable among employees at PT. Jambi Ekspres Televisi. This research uses a quantitative approach with Structural Equation Modeling (SEM-PLS) technique analyzed using SmartPLS 4.0. The sample consists of 30 respondents selected through saturated sampling. Data were collected using a Likert scale questionnaire that measures the variables of participative leadership, voice behavior, and knowledge sharing. The results of the study show that (1) participative leadership, voice behavior, and knowledge sharing are at a high category; (2) participative leadership has a positive and significant impact on voice behavior; (3) participative leadership has a positive and significant impact on knowledge sharing; (4) knowledge sharing has a positive and significant impact on voice behavior; and (5) knowledge sharing significantly mediates the relationship between participative leadership and voice behavior. This study recommends that PT. Jambi Ekspres Televisi enhance participative leadership practices by strengthening two-way communication and implementing a more structured knowledge management system to improve performance and collaboration among employees.